'A place for everything': Moral landscapes of 'swiftlet farming' in George Town, Malaysia. (December 2016) - Connolly, Creighton
Highlights: Develops the conceptual approach of landscape political ecology. Enhances understanding of the role of animals in shaping urban form and dynamics. Highlights the complex factors involved in managing human-animal relations in cities. Adds to understanding of politically and morally-infused claims to urban space. Abstract: This paper is based on 6 months of ethnographic, multi-sited research in Malaysia, and investigates the relatively recent phenomenon of edible birds' nest farming in urban areas ('swiftlet farming'). Swiftlet farms are typically converted shophouses or other buildings which have been modified for the purpose of harvesting the nests of the Edible-nest Swiftlet ( Aerodramus fuciphagus ). I use the controversy over urban swiftlet farming in the Malaysian city of George Town, Penang, to examine discourses used by key stakeholders to shape debates over the place of non-human animals in cities. By considering everyday experiences of urban swiftlet farming, I explore how this burgeoning industry is perceived amongst residents, and how it is deemed to be (in)appropriate within the political, economic and cultural landscape of George Town. Yet, I also consider how farmers have sought to contest these discourses on ideological and normative grounds. In so doing, I place the cultural animal geographies literature in conversation with emergent literature on landscape and urban political ecology. Such a framing allows for a critical evaluation of the controversies surrounding this case, and their implications for human-animal cohabitation in cities. The paper reflects on the implications of this case for how we regulate human-animal relations and live in contemporary cities, and the crucial role of animals in altering urban form, aesthetics and everyday life, particularly in non-Western contexts.